Antecedents and consequences of problematic smartphone use: A systematic literature review of an emerging research area - Busch, Peter André; McCarthy, Stephen (Computers in human behavior, 2021)
This article provides a systematic review of existing research on problematic smartphone use (PSU) to guide other researchers in search of relevant studies, and to propose areas for future research. In total, 293 studies were analyzed leading to the development of an overview model in the field of PSU, presenting findings on demographic factors, explanations for smartphone use and why this use becomes problematic, consequences of PSU, and how such use can be corrected. In addition, we considered in which contexts, with which methods, and with which theoretical lenses this stream of research has been studied to date. Smartphone use is most often explained by the smartphone design, and users' emotional health and their ability to control smartphone use. Our review suggests that people who are young, female, and highly educated are more prone to PSU. Emotional health issues are the most frequently identified consequence of PSU. Strategies for correcting PSU fall into three categories: information-enhancing, capacity-enhancing, and behavior reinforcement strategies. The studies on PSU are most often conducted using quantitative surveys with university and college participants considering their personal smartphone use. Whereas a variety of theoretical frameworks have been adopted to investigate PSU, they are often related to identifying factors explaining use and problematic use, and more seldom to analyze the findings. A future research agenda for PSU is proposed consisting of seven key research questions which can be investigated by researchers going forward. [Display omitted] •It is timely and important to summarize what we already know about PSU.•Research focuses on users, phone use, antecedents/consequences of PSU, and corrective measures.•The research area to date is presented including an integrated visual representation.•A future research agenda is proposed consisting of seven key research questions.